Is Effleurage Massage Effective to Reduce Menstrual Pain in Female Students? - Wanda Indriya Pramesti; Sudaryanto, Wahyu Tri (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Menstrual pain, or dysmenorrhoea, is common in young women worldwide under 25 years old. Elevated levels of prostaglandins in menstrual fluid induce contractions in the myometrium, leading to a decrease in uterine blood flow and resulting in uterine hypoxia. This hypoxia is the underlying cause of the painful cramping observed in primary dysmenorrhea. Massage is a non-pharmaceutical therapy that is hypothesized to be easily adoptable, with no side effects, and to have beneficial effects on pain. This study aimed to evaluate the effectiveness of effluerage massage in reducing menstrual pain in female students. Subjects and Method: A randomized controlled trial was conducted at Junior High School 23 of Surakarta in July 2023. Total sample of 50 2nd grade female student was selected by purposive sampling and divided into two groups. Intervention group received effluerage massage and control group received usual care. The dependent variable was menstrual pain. The independent variable was effleurage massage. Menstrual pain was measured using Numeric Ranting Scale (NRS). Pain difference between groups after intervention was examined using independent t test. Results: At the 6th follow-up period, the mean of menstrual pain score in the effleurage massage group (Mean 3.52; SD= 1.01) was significantly lower compared to the control group (Mean= 4.40; SD= 0.76), with a p-value of 0.001. Conclusion: Effleurage massage is effective to reduce menstrual pain in Junior High School female students. Keywords: effleurage massage, primary dysmenorrhea, menstrual pain, female adolescents